2021
DOI: 10.1186/s12872-021-02095-2
|View full text |Cite
|
Sign up to set email alerts
|

Different body parts’ fat mass and corrected QT interval on the electrocardiogram: The Fasa PERSIAN Cohort Study

Abstract: Background Previous studies suggested that obesity and fat mass are associated with QT interval prolongation, but the role of different body parts' fat mass is unclear. The associations between total and regional fat mass (FM) and corrected QT interval (QTc) were investigated for the first time in this study. Methods In this sub-analysis of Fasa PERSIAN cohort Study data, 3217 subjects aged 35–70 entered our study. Body fat mass was assessed by bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…An important aspect to discuss is the causes of the association of QT prolongation with BFP increase. Several studies have shown that QT interval prolongation is common in obesity, and it shortens with weight loss [ 26 , 71 ]. It seems that the distribution of adipose tissue also influences the values of the QT interval, with upper body obesity exerting a more marked effect [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important aspect to discuss is the causes of the association of QT prolongation with BFP increase. Several studies have shown that QT interval prolongation is common in obesity, and it shortens with weight loss [ 26 , 71 ]. It seems that the distribution of adipose tissue also influences the values of the QT interval, with upper body obesity exerting a more marked effect [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another field of investigation with multiple practical applications refers to the study of the impact of changes in body composition on electrical heart activity. A common finding of some research is that obesity and an increase in BFP are associated with a higher QT interval of the electrocardiogram (ECG) in young males [ 26 ]. Even in healthy normal-weight subjects, increased BMI is related to some electrocardiographic alterations: increasing P-wave length, leftward shifting of the electrical axis of the heart, and decreasing Sokolow–Lyon index [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first relates to the differences in baseline characteristics seen between the populations. Body fat mass, metabolic syndrome and its component, especially waist circumference and blood pressure, have been associated with electrocardiogram parameters and abnormalities [29,30] which may be factors associated to these differences in comparison to other populations. Second relates to the study sample selection between studies, as our study included individuals from a single center in Fasa city, and perhaps patients with more severe conditions are referred to centers in the main city of the province (Shiraz city).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the prevalence of QTc prolongation was significantly higher among patients who experienced CAE from the start of TKI therapy to the cardiovascular evaluation than among those who did not. Any change in the QT interval can reflect abnormalities in the two phases of the cardiomyocyte electrical cycle [36]. In addition, QTc prolongation is associated with arrhythmia, myocardial infarction, left ventricular dysfunction, and stroke [37][38][39].…”
Section: Discussionmentioning
confidence: 99%